Improvement of Bread Nutrition With The Addition of Coffee Silverskin as a Source Of Dietary Fiber And Antioxidants - Rizkaprilisa, Windy; Hapsari, Martina Widhi; Paramastuti, Ratih; Pebrianti, Suci Apsari (University of Sultan Ageng Tirtayasa, 2023)
Prevention of obesity can be done by reducing the intake of foods high in carbohydrates and fats, then replacing them with high dietary fiber. Silverskin is a by-product of coffee beans with dietary fiber and antioxidants, which can potentially treat obesity. Indonesia has a typical regional bread,